(untitled) (Annals of Medical Research, 2021)
Aim: Gastrostomy tubes provide nutritional access in patients with impaired oral intake. Gastrostomy tubes can be inserted with endoscopy or fluoroscopy assistance. The aim of this study was to describe the clinical features and complications of fluoroscopy-guided gastrostomy tube insertion and to compare these complications with those of the endoscopy-assisted gastrostomy technique.Material and Methods: A retrospective data analysis was performed for gastrostomy tube placement procedures. Patients’ age, gender, medical, neurological, and surgical diseases, major and minor complications, mortality rates, and length of hospital stay were compared between fluoroscopy-guided and endoscopy-guided pull-type gastrostomy tube placement. Results: The medical records of 92 patients (60 male, 32 female; mean age ± SD: 63.1 ± 15.8 years; range: 24-92 years) who underwent endoscopy-guided (n=50) or fluoroscopy-guided (n=42) gastrostomy tube placement were reviewed. The indications for gastrostomy tube insertion mainly included neurological disease (n=39, 78%), such as cerebrovascular accident (n=22, 44%), in the endoscopy group and surgical disease (n=33, 73.3%), such as head and neck cancer (n=27, 60%), in the fluoroscopy group. There were no mortalities related to gastrostomy tube insertion in either group. There was no significant difference between the major complication rates of the two groups (P=0.62). The minor complication rate was higher in the endoscopy group (P=0.03). One patient in the fluoroscopy group required surgical intervention to treat a complication related to gastrostomy insertion.Conclusion: Gastrostomy tube insertion via both endoscopy and fluoroscopy guidance provides a safe route for nutrition delivery. Fluoroscopy-guided placement of pull-type gastrostomy tubes is a reliable technique and should be the first choice for gastrostomy tube placement, particularly for patients with head and neck tumors in whom endoscopic placement is technically difficult.